Selected Papers from the 19th International Conference on Calorimetry in Particle Physics (CALOR 2022) - Salvatore, Fabrizio; De Santo, Antonella; Vivarelli, Iacopo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains a summary of what has been presented at the 19th "Calorimetry for High Energy Physics Experiment" (CALOR) conference, which was held at the University of Sussex (Brighton, UK) in May 2022. The state of the art of particle detection, as well as of simulation tools for particle interactions with material, is presented and discussed by world leaders in the Research & Development of particle detectors, as well as early career researchers, sparking very exciting conversations within the detector development community during the five days of the conference.